Forms of Legal Protection for the Victim - Ayoub Hassan, Researcher. Atyaf; Omar Muslim, Assist .Prof. Aseel (Basra studies journal, 2025)
This study examines the various forms of legal protection, including prior protection, which safeguards witnesses, experts, or informants from assault, and subsequent protection, which aims to protect the victim or the person harmed by the crime from deteriorating health or financial hardship that may result after the assault. Accordingly, the study sheds light on the extent to which criminal laws sufficiently provide such protection, or whether they fall short. The research is divided into two sections: the first is devoted to prior legal protection and its measures, while the second addresses subsequent legal protection and its mechanisms. The study reached several findings and recommendations, the most important of which is that, although Iraqi criminal law has made significant progress in providing protection to victims of crimes, it still does not offer protection at the required level. Despite the existence of various legislations enacted by the Iraqi legislator concerning victims, these laws suffer from notable gaps and deficiencies. Therefore, it is necessary for the Iraqi legislator to establish a robust protective framework that ensures the prevention of assaults on victims and helps them recover and rebuild their lives afterward.